2020
DOI: 10.1093/ejo/cjaa013
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of external apical root resorption with clear aligners and pre-adjusted edgewise appliances in non-extraction cases: a systematic review and meta-analysis

Abstract: Summary Objective The aim of this study was to evaluate and compare the amount of external apical root resorption (EARR) observed during the orthodontic treatment with pre-adjusted edgewise appliance (PEA) or clear aligner therapy (CAT) and with 2D or 3D radiographic methods of measuring the root resorption. Search strategy and selection criteria A search of PubMed MEDLINE, Scopus, Cochrane C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 26 publications
0
37
1
1
Order By: Relevance
“…14 Various factors including biological and mechanical elements are responsible for the initiation of EARR and its progress during orthodontic tooth movement. 15,16 The most common teeth to undergo EARR are the maxillary incisors and maxillary and mandibular canines, with the average amount of 0.2 to 2.93 mm. The error level of periapical radiographs is four times less than cephalometry radiographs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Various factors including biological and mechanical elements are responsible for the initiation of EARR and its progress during orthodontic tooth movement. 15,16 The most common teeth to undergo EARR are the maxillary incisors and maxillary and mandibular canines, with the average amount of 0.2 to 2.93 mm. The error level of periapical radiographs is four times less than cephalometry radiographs.…”
Section: Discussionmentioning
confidence: 99%
“… 14 Various factors including biological and mechanical elements are responsible for the initiation of EARR and its progress during orthodontic tooth movement. 15 , 16 The most common teeth to undergo EARR are the maxillary incisors and maxillary and mandibular canines, with the average amount of 0.2 to 2.93 mm. The possible controversy regarding the average amount of EARR between studies is mostly due to difference in sample size, individual patient characteristics, type of the tooth considered for the study, type of orthodontic tooth movement, and the measurement method.…”
Section: Discussionmentioning
confidence: 99%
“…The current evidence from one systematic review concluded that the use of clear aligners will not avoid root resorption, but both the incidence and severity of resorption could be lower compared with results of fixed appliance treatment (Fang et al, 2019). In addition, a further systematic review (Gandhi et al, 2021) found that neither preadjusted edgewise appliance or clear aligner therapy resulted in clinically significant root resorption (1 mm) of the maxillary incisors. However, while the amount of root resorption observed in relation to the maxillary incisors was not significantly different between the two treatment modalities, the maxillary right lateral incisor had significantly more root resorption with fixed appliance therapy (Gandhi et al, 2021).…”
Section: Root Resorptionmentioning
confidence: 99%
“…In addition, a further systematic review (Gandhi et al, 2021) found that neither preadjusted edgewise appliance or clear aligner therapy resulted in clinically significant root resorption (1 mm) of the maxillary incisors. However, while the amount of root resorption observed in relation to the maxillary incisors was not significantly different between the two treatment modalities, the maxillary right lateral incisor had significantly more root resorption with fixed appliance therapy (Gandhi et al, 2021).…”
Section: Root Resorptionmentioning
confidence: 99%
“…As more and more adult patients are undertaking orthodontic treatment, the emphasis for esthetic treatment modalities has increased. In addition to being esthetically pleasing, clear aligners have the advantage of applying low forces on the teeth, and thus can potentially lead to decreased root resorption as compared to fixed orthodontic appliances [23] . Over the years, the type of malocclusions that can be treated with clear aligners has increased because of the use of mini-implants with aligners.…”
Section: Mini-implants and Aligner Therapymentioning
confidence: 99%